Epoka Oświecenia – nieustające źródło „światła” czy okres błędów i wypaczeń zachodniego świata? - Drozdowicz, Zbigniew (Człowiek i Społeczeństwo, 2015)
In my reflections I relate to the disputes concerning the philosophical heritage of the Enlightenment period. I refer to the two significantly different positions concerning this issue, that of the liberals and of communitarians. The former tend to have a generally positive attitude towards the achievements of the period, taken to constitute a cultural breakthrough in the thinking of man, his needs and ways of satisfying them. The latter, however, evaluate the period negatively, and even consider it to be an acceleration in the loss of culturally important values and qualities. Both of them assume that an important role in the cultural changes has been played by philosophers – only that the former think it was a positive role, while the latter find it negative.